Perancangan Aplikasi Penerimaan dan Penugasan Personil Pengamanan PT. Siap Andalan Paramitra Berbasis Android - Agus Kodir Arifin (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2019)
On proof to this present time of development f information technologies the increasing. One of the example was is manifest that develop this kind of technology such as computer, smartphones today plays an important role in various fields, one of which is the field of information delivery. PT Siap Andalan Paramitra is engaged in security service provider (BUJP) and is facing one problem, namely the lack of coordinated information delivery between prospective job applicants and new employee admissions. Then we need a system of information delivery that is expected to be able to overcome the problem. The problem discussed is how to make the Information System with an Android application. The method used is grounded research, which is a research method based on facts and uses comparative analysis with the aim of holding empirical generalizations, defining concepts, proving theories, developing theories, collecting and analyzing data at the same time. This method is an attempt to get a solution to the problem of Information Systems Acceptance and Assignment of Security Personnel PT. Siap Andalan Paramitra